Penanaman Karakter Moderat Santri Melalui Program Pendidikan Diniyah Formal Pondok Pesantren Nurul Jannah Banjarmasin - Ishaac, Muhamad (Akademika : Jurnal Keagamaan dan Pendidikan, 2023)
The importance of cultivating moderate character in santri as a result of efforts to prevent radicalism and terrorism in Indonesia as well as instilling moderate character in santri so that they can live in harmony in Indonesia within Indonesia's diversity. The formal diniyah education program was designed by the Ministry of Religion of the Republic of Indonesia to produce a moderate cadre of ulama with the characteristics of the six moderate characteristics of the students of the Ministry of Religion of the Republic of Indonesia, implemented at the Nurul Jannah Islamic Boarding School in Banjarmasin and capable of producing a cadre of ulama who are broad-minded and have a moderate character. The focus of the problem in this research is the form of cultivating the moderate character of santri which includes six moderate characters of santri of the Ministry of Religion of the Republic of Indonesia through the formal diniyah education program at the Nurul Jannah Islamic Boarding School, Banjarmasin, as well as the factors that support and hinder its implementation. Data collection techniques for this research include using interviews, observation and documentation. cultivating moderate character for santri which includes six moderate character traits for santri. The Ministry of Religion of the Republic of Indonesia uses character cultivation methods such as example, habituation, giving advice, targhib wa tahzib, and the takzir method which is in accordance with the principles of cultivating moderate character of the Republic of Indonesia Ministry of Religion. Supporting factors include cooperation from all parties involved, intensive character cultivation, and strong determination and motivation from the students. Meanwhile, inhibiting factors are the lack of quantity and quality of teachers, excessive use of devices outside school hours, and lack of cooperation from parents.